SOCIAL ENGINEERING IN THE IMPLEMENTATION OF FOREST AND LAND REHABILITATION IN GIRIMULYO VILLAGE, LAMPUNG PROVINCE - Gunawan, Rhezandhy; Febryano, Indra Gumay; Bantara, Idi; Yuwono, Slamet Budi (Forestry Study Program University Of Mataram, 2024)
Social engineering in conflict-affected communities is critical to the success of forest and land rehabilitation. The purpose of this study is to describe social engineering in the implementation of RHL based on local superior plants. Data collection was carried out by observation, interviews and documentation studies. The collected data were analyzed descriptively to explain social engineering in the implementation of forest rehabilitation. The results of this study show that social engineering is carried out using the principles of collaborative management and listening to what the community wants (bottom up). Coordination between relevant stakeholders needs to be improved in order to avoid differences of opinion in the implementation of activities and the need to increase the human resources of the Agro Mulyo Lestari Forest Farmer Group in order to facilitate the administrative process of managing the administration.